Molecular Docking Study of Active Compounds in White Radish (Raphanus sativus L.) on Progesterone Receptor (PRG) as an Anti-Cancer Agent - Arfinda Hanung Saputri; Wahyu Yuliana Solikah; Daru Estiningsih; Nurul Jannah (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
White radish (Raphanus sativus L.) contains various bioactive compounds that may contribute to different biological activities. This study aimed to evaluate the interaction of selected white radish compounds with the progesterone receptor (PRG) using an in silico molecular docking approach as a preliminary step for anticancer screening. Molecular docking was performed using AutoDock 4, BIOVIA Discovery Studio, and PyMOL to assess binding affinity, Root Mean Square Deviation (RMSD), and amino acid interactions. Among the five tested white radish compounds, glucoraphanin had the best docking score (–4.8 kcal/mol) for the progesterone receptor. However, this binding affinity remained weaker than that of the control ligand tamoxifen (–6.19 kcal/mol). Molecular interaction analysis indicated that glucoraphanin formed interactions with several key amino acid residues within the receptor binding site. Docking validation produced an RMSD value of <2 Å, indicating acceptable docking reliability. These findings suggest that glucoraphanin from white radish may interact with the progesterone receptor and warrant further investigation. Nevertheless, further experimental studies are required to confirm its potential biological activity